DESKRIPSI ANALISIS KEBUTUHAN MEDIA PEMBELAJARAN IPA KELAS VII MTsN 1 SELUMA - Junaini, Junaini; Nursaadah, Euis; Firdaus, M. Lutfi (UNIB Press, 2024)
The aim of this research was to analyze the needs of students in science learning at MTsN 1 Seluma, Bengkulu. The method used was a survey via questionnaire with 9 questions given to 30 class VII students. The survey results show that 100% of students have textbooks/handbooks, 100% have smartphones, 93% have difficulty studying material that only comes from books, so 100% of students look for other materials besides books from school to help understand the material. science via the internet, therefore 100% of students need interesting alternative learning media. In science learning, students agree that there is Android-based learning media for science material, especially environmental pollution material. Students want learning to be adapted to current developments and technology, interesting, interactive, and can be accessed anytime and anywhere via smartphone. Implementation of media in the form of Android-based applications can be an alternative to empower students' use of technology and to improve the quality of science learning.